Ruminal Phages – A Review - Lobo, Richard R.; Faciola, Antonio P. (Frontiers in Microbiology, 2021)
The rumen ecosystem is a complex and dynamic environment, which hosts microorganisms including archaea, bacteria, protozoa, fungi, and viruses. These microorganisms interact with each other, altering the ruminal environment and substrates that will be available for the host digestion and metabolism. Viruses can infect the host and other microorganisms, which can drive changes in microorganisms’ lysis rate, substrate availability, nutrient recycling, and population structure. The lysis of ruminal microorganisms’ cells by viruses can release enzymes that enhance feedstuff fermentation, which may increase dietary nutrient utilization and feed efficiency. However, negative effects associated to viruses in the gastrointestinal tract have also been reported, in some cases, disrupting the dynamic stability of the ruminal microbiome, which can result in gastrointestinal dysfunctions. Therefore, the objective of this review is to summarize the current knowledge on ruminal virome, their interaction with other components of the microbiome and the effects on animal nutrition.